Fetal and neonatal bilirubin metabolism - Itoh, Susumu; Okada, Hitoshi; Koyano, Kosuke; Nakamura, Shinji; Konishi, Yukihiko; Iwase, Takashi; Kusaka, Takashi (Frontiers in Pediatrics, 2023)
Human fetal and neonatal bilirubin metabolism is centered on 4Z,15Z-bilirubin IXα (BR) due to the extremely low BR conjugating capacity of the liver. BR is a unique, highly lipophilic substance with physiological and toxic effects in the cell membranes of organs and body tissues. The fetus excretes BR through the placenta to the maternal circulation. After birth, BR is thought to act as an antioxidant against the increase in reactive oxygen species caused by the rapid increase in oxygen concentration during the adaptation process from in amniotic fluid to in air. However, bilirubin encephalopathy is a toxic effect of bilirubin. Due to the lipophilic nature of BR, it must be bound to a carrier to be distributed to various parts of the body by hydrophilic blood. This carrier of BR is human serum albumin (HSA). In humans, BR can be excreted efficiently after undergoing photochemical reactions upon high affinity binding to HSA. HSA also plays an important role in the prevention of bilirubin encephalopathy. This review focuses on the developmental and physiological role of bilirubin metabolism during the fetal and neonatal periods.